That summer ebook A novel. - Weiner, Jennifer (2021)
INSTANT NEW YORK TIMES BESTSELLER Named a Notable Work of Fiction by The Washington Post From the #1 New York Times bestselling author of Big Summer comes another "ideal beach read, full of secrets and complicated female friendships" ( Cosmopolitan ). Daisy Shoemaker can't sleep. With a thriving cooking business, full schedule of volunteer work, and a beautiful home in the Philadelphia suburbs, she should be content. But her teenage daughter can be a handful, her husband can be distant, her work can feel trivial, and she has lots of acquaintances, but no real friends. Still, Daisy knows she's got it good. So why is she up all night? While Daisy tries to identify the root of her dissatisfaction, she's also receiving misdirected emails meant for a woman named Diana Starling, whose email address is just one punctuation mark away from her own. While Daisy's driving carpools, Diana is chairing meetings. While Daisy's making dinner, Diana's making plans to reorganize corporations. Diana's glamorous, sophisticated, single-lady life is miles away from Daisy's simpler existence. When an apology leads to an invitation, the two women meet and become friends. But, as they get closer, we learn that their connection was not completely accidental. Who IS this other woman, and what does she want with Daisy? From the manicured Main Line of Philadelphia to the wild landscape of the Outer Cape, written with Jennifer Weiner's signature wit and sharp observations, That Summer is a "compelling, nuanced novel" (Maureen Corrigan, The Washington Post ) about surviving our pasts, confronting our futures, and the sustaining bonds of friendship.